Cyber Space: A Dangerous World for Children (Analysis on Transnational Online Child Pornography) - Septianita, Hesti; Rachmie, Synthiana (International Journal of Latin Notary, 2024)
International community has been paying attention on welfare of children for decades by passing laws regulating international actions as the endeavours to promote and achieve the goals on maintaining the safety and welfare of children of the world. Ironically, this crime of cyber-pornography involving underage individuals is not yet internationally regulated as a transnational organized crime making the perpetrators free to do this horrendous doing while children, the victims are still unprotected even though international law on child protection has been promulgated and in force. This writing will discuss crimes committed against children, mainly focused on online sexual abuse and exploitation with modus operandi structured and organized. The research aims to propose a notion on new category of transnational organized crime which is cyber child pornography by analyzing the elements of crime of transnational online child pornography. The research is conceptual research with philosophical and normative approaches. The idea to bring about the crime into a transnational organized crime should be an immediate action by promulgating an international legal instrument in effect considering the severity of the crime against the children’s future life.